The Existence Of Loyalty In Indonesia Ministery Education Regulation On Electronic Text Book. (Study Of Vocational High School’s Electronic Text Book In Bandung)*) - Zulganef Sutan Sati; Usin Susanto (Jurnal Manajemen Teori dan Terapan | Journal of Theory and Applied Management, 2013)
The Indonesian government believes that textbooks play a strategic role in improving the quality of primary and secondary education (Regulation of the Minister of National Education of the Republic of Indonesia No.11 of 2005). Nevertheless, Abdulkarim (2010) revealed that the quality of school textbooks, either in junior or vocational / high school is very low. The contradiction between Regulation of the Minister of National Education Regulation goal and Abdulkarim (2010), and some previous research, such as Heskett et al. (1997), and Dimitriades (2006) motivates this study to analyze the effect of satisfaction to commitment and loyalty of vocational teachers in Bandung. The results showed that there was no correlation between satisfaction and the commitment and between the commitment and loyalty, but there is a significant direct correlation between satisfaction and loyalty. This shows that users of textbooks as the government policy consumers has loyalty in the sense will do its use continuously, but the loyalty is not based on a commitment, but only based on satisfaction.This is suggests that vocational high school teachers are satisfied with the textbook but don’t want to rely on Regulation of National Education Minister, since commitment is defined by Dwyer et al. (1987), Morgan and Hunt (1994), and Pritchard et al. (1999) as a stable seeking and defensive attitude towards not to change a choice. They are easy to change attitudes through using of Electronic Text Boook (ETB) as teaching materials. The Authors also revealed some limitations and recommendations